2021
DOI: 10.1371/journal.pone.0254321
|View full text |Cite
|
Sign up to set email alerts
|

Metformin intervention ameliorates AS in ApoE-/- mice through restoring gut dysbiosis and anti-inflammation

Abstract: Atherosclerosis (AS) is closely associated with chronic low-grade inflammation and gut dysbiosis. Metformin (MET) presents pleiotropic benefits in the control of chronic metabolic diseases, but the impacts of MET intervention on gut microbiota and inflammation in AS remain largely unclear. In this study, ApoE-/- mice with a high-fat diet (HFD) were adopted to assess the MET treatment. After 12 weeks of MET intervention (100mg·kg-1·d-1), relevant indications were investigated. As indicated by the pathological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 85 publications
3
14
0
Order By: Relevance
“…We also found a marked alteration in levels of Romboutsia, with WTD-fed mice showing an increase vs. chow-fed mice, while mice fed with WTD + Miltefosine showed marked reduction in Romboutsia levels vs. WTD-fed mice. Previous studies have shown a differential abundance of Enterobacteriaceae, Bacteroides, and Romboutsia in atherosclerosis [51][52][53][54] . One of the mechanisms by which Miltefosine can alter gut microbiota is via its antibacterial properties 8 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We also found a marked alteration in levels of Romboutsia, with WTD-fed mice showing an increase vs. chow-fed mice, while mice fed with WTD + Miltefosine showed marked reduction in Romboutsia levels vs. WTD-fed mice. Previous studies have shown a differential abundance of Enterobacteriaceae, Bacteroides, and Romboutsia in atherosclerosis [51][52][53][54] . One of the mechanisms by which Miltefosine can alter gut microbiota is via its antibacterial properties 8 .…”
Section: Discussionmentioning
confidence: 87%
“…Given that Miltefosine had been used in humans for decades, it can be potentially used in lower doses as a stand-alone or as an adjuvant to LDL lowering therapies to treat inflammatory diseases such as atherosclerosis. In support of Miltefosine as a potential anti-atherosclerotic molecule, previous studies have shown that alterations in gut microbial species, either via dietary interventions with chemical compounds such as Metformin and resveratrol or via gavage inoculation, can impact the progression of atherosclerosis 51,54,56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that phyla Bacteriodetes and Firmicutes were kept predominantly in diverse groups, which are paralleled with previous studies ( 18 , 23 , 32 ). An increase in Firmicutes / Bacteriodetes ratio is closely related to chronic metabolic diseases [( 24 , 25 , 41 )]. In this study, the increased ratio of Firmicutes / Bacteriodetes in AS was rectified by the dietary FO administration, suggesting that FO could markedly modulate the gut microbiota by decreasing the predominant Firmicutes / Bacteriodetes in phylum level ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is extremely necessary to investigate the mechanism of RILI, and develop new drugs. NaB has been reported, by a large number of studies, that exerts potential activities of anti-radiation toxicity ( 11 , 12 ), anti-inflammation ( 45 47 ), immunomodulation ( 48 , 49 ), and anti-tumor ( 50 52 ). The anti-lung cancer effect of NaB has been proved in our preliminary study ( 21 ).…”
Section: Discussionmentioning
confidence: 99%